2002
DOI: 10.1007/s00784-001-0139-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of amelin and trauma-induced dentin formation

Abstract: According to recent studies, amelin (ameloblastin, sheathlin) is expressed in young odontoblasts at the initiation of dentin formation during odontogenesis. The purpose of the present investigation was to study whether amelin is also expressed at the onset of traumainduced reparative dentin formation. The mandibular developing first molars of 5-day-old rats were surgically taken out, and their pulp tissue briefly separated from the inner dentin surface and immediately repositioned. Then the teeth were re-impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
5
22
0
10
Order By: Relevance
“…Our group has previously shown that rAMBN (20) and 5-HT (34) enhance proliferation and differentiation of mesenchymal stem cells. The rIFN-Y-enhanced promoter activity in the M2-10B4 cell line may be linked to our previous findings, where rAMBN strongly induced the IFN-Y pathway in osteoblasts (20) and DEX is a known factor in osteogenic differentiation (35), and strengthens the suggestion that AMBN may act as a signalling molecule in developing hard tissues (5,10,14,18,20,36).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our group has previously shown that rAMBN (20) and 5-HT (34) enhance proliferation and differentiation of mesenchymal stem cells. The rIFN-Y-enhanced promoter activity in the M2-10B4 cell line may be linked to our previous findings, where rAMBN strongly induced the IFN-Y pathway in osteoblasts (20) and DEX is a known factor in osteogenic differentiation (35), and strengthens the suggestion that AMBN may act as a signalling molecule in developing hard tissues (5,10,14,18,20,36).…”
Section: Discussionsupporting
confidence: 88%
“…The biological function of AMBN remains obscure, and it is now documented that AMBN expression is not restricted to enamel formation (5,6,10). In odontogenesis, Ambn is believed to be implicated in enamel biomineralization (11)(12)(13) and in interactions between the ameloblasts and the extracellular matrix (14)(15)(16).…”
mentioning
confidence: 99%
“…Preliminary results showed that FGF-9 can induce early, significant Ameloblastin, Amelogenin and Osteocalcin expression in mesenchymal cells cultured with FGF-9 (Additional file 1). These findings were concurrent with the gene expression of mesenchymal origin cells, such as odontoblasts, during the early stage of tooth development [19,20]. In addition, FGF-9 can induce early expression of the homeobox protein Msx genes Msx-1 in mesenchymal cells (Additional file 1), which is consistent with previous research [14].…”
Section: Fgf-9 Promotes Tooth Germ Developmentsupporting
confidence: 88%
“…Mesenchymal cells were cultured in vitro and FGF-9 (25 ng/ml) was added to the experimental group. FGF-9 significantly upregulated Ameloblastin and Amelogenin expression [19,20]. The homeobox protein Msx genes Msx-1 and Msx-2 (although expressed at low levels), and Osteocalcin were also upregulated after initial contact with FGF-9.…”
Section: Additional Filesmentioning
confidence: 96%
“…On the basis of the timing and location of expression [23,24], Ambn could function in extracellular signaling during sequential and reciprocal developmental processes, cell adhesion, and/or act as crystal nucleator during dentin mineralization. Ambn expression has also been demonstrated during trauma-induced reparative dentin formation in adult teeth, suggesting that this protein also is expressed as a part of reparative processes in the dental pulp [25].…”
mentioning
confidence: 99%